2021
DOI: 10.1177/0308518x21989702
|View full text |Cite
|
Sign up to set email alerts
|

Country-of-origin-specific economic capital in neighbourhoods: Impact on immigrants’ employment opportunities

Abstract: Does living in an area characterized by high concentrations of residents of the same country-of-origin deprive ethnic minority groups, or does potential access to an extended country-of-origin-specific network stimulate their integration? This paper takes a new approach to analysing the potential of country-of-origin-specific economic capital in neighbourhoods to increase employment opportunities. We add to the ‘ethnic enclave’ debate by measuring country-of-origin-specific economic capital as the rate of empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…Language and cultural barriers are limited, and recent research has shown that very positive effects of such situations should be expected when the already settled individuals have relatively strong economic positions. In other words, the presence of 'own-group' co-residents in their immediate area who are employed themselves would create ideal conditions for newcomers to get access to the labour market as well (Kadarik et al, 2021). Such situations of co-location of individuals of the same country of origin should therefore not automatically be judged negatively.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Language and cultural barriers are limited, and recent research has shown that very positive effects of such situations should be expected when the already settled individuals have relatively strong economic positions. In other words, the presence of 'own-group' co-residents in their immediate area who are employed themselves would create ideal conditions for newcomers to get access to the labour market as well (Kadarik et al, 2021). Such situations of co-location of individuals of the same country of origin should therefore not automatically be judged negatively.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, staying put in their own socio-cultural spatial 'bubble' and not crossing borders to other groups may potentially hinder full integration in the recipient society (Massey and Denton, 1987;Wilson, 1987). In addition, there are indications that 'own-group' migrants may be helpful, but especially if the already settled migrants also occupy a good position in society and are employed (Kadarik et al, 2021).…”
Section: Debates and Literaturementioning
confidence: 99%
“…Young people with not so developed forms of capital exhibit risks to become trapped in more precarious housing segments and to suffer several setbacks (Hochstenbach & Boterman, 2015). In addition, the availability of supportive social networks in one's neighbourhood-especially important for ethnic minorities and low-income households, may lower incentive for moving, or lead to residential choices where the supportive clusters exist (Kadarik et al 2021;Miltenburg, 2015;Phillips, 2006). The level of residential clustering tends to be especially high for migrants upon arrival, especially when arriving from a low-income country (Macpherson & Strömgren, 2013), but the longer duration of residing in a certain neighbourhood also seems to decrease the incentive to move (Vogiazides, 2018).…”
Section: Main Drivers Of Residential Mobilitymentioning
confidence: 99%
“…Not least, in relation to the challenges of measuring neighbourhood effects, the issue of spatial scale emerges as a key aspect (R. Andersson, & Musterd, 2010;Kadarik, Miltenburg, Musterd, & Östh, 2021). As argued by Östh and Türk (2020; see also Grannis, 1998Grannis, , 2005Kasarda & Janowitz, 1974), this points in the direction of knowing more, not only about where people reside but also about how infrastructure and accessibility shape a neighbourhood's conditions for its residents.…”
Section: Introductionmentioning
confidence: 99%